Союзное государство России и Беларуси: проблемы и перспективы - Блохин, В.Н.; Blochin, V.N. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The article examines the main destinations of integration of Russia and Belarus in the framework of the Union State. Draws attention both the achievements and successes in foreign policy, economic cooperation, as well as the problems of further integration.
Union State of Russia and Belarus: problems and perspectives
В.Н. Блохин, магистр ист.н., препод. УО «Белорусская государственная сельскохозяйственная академия» (Беларусь, Могилевская обл., г.Горки)
Keywords: Union State; integration; political system; cooperation